The translation of multilingual films: Modes, strategies, constraints and manipulation in the Spanish translations of It’s a Free World … - De Higes Andino, Irene (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
British films narrating stories of migration and diaspora are usually multilingual, as directors and scriptwriters wish to depict the linguistic diversity characteristic of today’s British society. But what happens when multilingual films are translated into other languages for distribution abroad? Is multilingualism maintained in the target versions of the film? And when multilingualism is omitted or substituted, is filmic manipulation technically or ideologically bounded? This paper develops a model of analysis which opens up a path in the study of the translation of multilingualism in films by establishing a relationship between translation modes, translation strategies and constraints. I then put the model for analysis to the test in a case study of the dubbing and subtitling into Spanish of one British migration and diasporic film, It’s a Free World … by Ken Loach (2007).